Meta Analysis: Factors Affecting Health Care Service on Outpatient’s Satisfaction in Hospital - Noviani, Desi; Purwantanti, Titis Cipta; Risnasari, Annisa; Murti, Bhisma; Munawaroh, Siti Mar'atul (Journal of Health Policy and Management, 2025)
Background: Patient satisfaction with health services is very important to measure the level of health services offered to patients and the implementation of health services in hospitals. Patient expectations about service quality are also related to service perceptions and when patients have a good impression, patients' clinical experiences and outcomes are more likely to have positive responses. The aim of this study is to analyze the influence of health service factors on the level of satisfaction of outpatients in hospitals based on the results of several previous studies using meta-analysis.Subjects and Method: This research is a systematic review and meta-analysis based on data obtained through various databases including Google Scholar, PubMed, ResearchGate and Science Direct. This study used articles that were published from 2014 to 2022. The article search was carried out by considering the eligibility criteria defined using the PICO model. Population: outpatients. Intervention: comfortable waiting room, short waiting time, drug availability and payment status (free). Comparation: uncomfortable waiting room, long waiting time, no medicine available and payment status (Out of Pocket). Outcome: patient satisfaction. This article was collected within 1 month with the following keywords used: "Waiting Room" AND "Waiting Time" AND "Drug" AND "Payment Status" AND "Outpatient Health Services" OR "Satisfaction" AND "Cross Sectional Study". The articles included in this research are full text articles with a cross-sectional study design. This article was collected using a PRISMA flow diagram and analyzed using the Review Manager 5.3 application.Results: Meta-analysis of 16 articles using a cross-sectional research design from the countries of Ethiopia and Fiji. Total sample 15,453. Patient satisfaction increases with a comfortable waiting room (aOR= 2.54; 95% CI= 2.01 to 3.21; p < 0.001), short waiting time (aOR= 2.97; 95% CI= 1.62 to 5.47; p < 0.001), good availability of medicines. complete (aOR= 2.01; 95% CI= 1.55 to 2.60; p <0.001), and payment status (free) (aOR= 1.99; 95% CI= 1.34 to 2.95; p <0.001).Conclusion: Outpatient satisfaction in hospitals increases with the comfort of the waiting room, short waiting time, availability of medicines, and payment status (free).